PENUANG SABUN CAIR OTOMATIS BERBASIS MIKROKONTROLER ATMEGA16 - , THORIQ AZIZ A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, technology development become more and more advanced. All of these technologies have the same goal, namely to facilitate human in doing their activities. Pour liquid soap manually or semi-automatically maybe less effective. To be able to create automated systems and its applications can be arranged upon user, infrared sensor module can be used, and it will detect the hand when it will take the soap. After that, the result of sensor readings will be processed in microcontroller, the output will activate relay that will operate central lock for emphasis and casting automatically. So, these activities become more efficient and practical.